Tuning the Structure and Properties of Ultra-Low Cross-Linked Temperature-Sensitive Microgels at Interfaces via the Adsorption Pathway - Schulte, M Friederike (Langmuir : the ACS journal of surfaces and colloids, 2019)
The structure of poly(N-isopropylacrylamide) (PNIPAM) microgels adsorbed onto a solid substrate is investigated in the dry and hydrated states by means of atomic force microscopy (AFM). We compare two different systems: a regularly cross-linked microgel containing 5 mol % cross-linker and ultra-low cross-linked microgels (ULC) prepared without a dedicated cross-linker. Furthermore, we compare three different adsorption processes: (i) in situ adsorption from solution, (ii) spin-coating, and (iii) Langmuir-Blodgett deposition from an oil-water interface. The results demonstrate that the morphology and the temperature-induced collapse of microgels adsorbed onto a solid substrate are very different for ultra-low cross-linked microgels as compared to regularly cross-linked microgels, despite the fact that their general behavior in solution is very similar. Furthermore, the morphology of ULC microgels can be controlled by the adsorption pathway onto the substrate. Absorbed ULC microgels are strongly deformed when being prepared either by spin-coating or by Langmuir-Blodgett deposition from an oil-water interface. After rehydration, the ULC microgels cannot collapse as entire objects, instead small globules are formed. Such a strong deformation can be avoided by in situ adsorption onto the substrate. Then, the ULC microgels exhibit half-ellipsoidal shapes with a smooth surface in the collapsed state similar to the more cross-linked microgels. As ULC microgels can be selectively trapped either in a more particle-like or in a more polymer-like behavior, coatings with strongly different topographies and properties can be prepared by one and the same ultra-low cross-linked microgel. This provides new opportunities for the development of smart polymeric coatings